Heterodox and Orthodox Discourses in the Case of Lyme Disease: A Synthesis of Arguments. (September 2019) - Hinds, Kate; Sutcliffe, Katy
In this article, we examine the arguments made by authors of published academic articles concerning the debates surrounding chronic Lyme disease (CLD). CLD is an example of a contested condition and shares problems of legitimacy with other medically unexplained conditions such as chronic fatigue syndrome. We use a critical discourse analysis (CDA) approach to understand the arguments of the authors to establish the legitimacy, or not, of a CLD diagnosis. This enabled us to make sense of the nature of the stalemate between patient groups and advocates of the medical establishment, as performed by authors of academic articles. In this article, we bring together the arguments to explain the polemical debate and to support accounts that avoid the impasse to give us greater insight into the experience of chronic illness.